(untitled) (International Journal of Physiotherapy, 2024)
Background: Disaster health management is the management of concerns related to the health of populations and medical facilities before, during, and after a disaster. This paper aims to estimate the contribution of physiotherapy professionals in disaster health by literature search and bibliometric study. Methods: The review is devoted to identifying physiotherapist competencies in disaster settings and the possible possibilities of their usage in emergency medical teams. The study underlines the shortcomings in the existing literature review examining this issue and underscores the need to strengthen physiotherapists’ disaster health management competencies further. Therefore, one needs to take cognizance of the diverse range of skills that physiotherapists possess to enhance their function in emergency response units and preparedness and response to disasters. Results: The articles reviewed totaled 654 of them on Disaster Health Management in Physiotherapy with increased research activity observed which is spearheaded by the U.S while Monash University was found to have contributed the most. Some of the key themes that came out were; education, competency, and physiotherapy with Physical Therapy journal publishing most articles. Conclusion: This study covers general background information, areas of interest, and recent developments in Disaster Health Management and Physiotherapy Competencies. According to the analyzed literature, there is evidence that the amount of work done in these fields is increasing, and there are good opportunities to share information among researchers, institutions, and countries.